The Development of Gender Identity, Gender Roles, and Gender Relations in Gifted Students. (April 2015) - Kerr, Barbara A.; Multon, Karen D.
<x xml:space="preserve">Abstract</x> This article describes the interaction of giftedness with gender identity, gender role, and gender relations. The authors explored ways in which many gifted educational practices are gendered, a model for the development of talent in the context of gender and gender relations, and ways of reducing gender inequities in the realization of potential for both male and female students. Issues that are unique to gifted individuals are aligned with suggestions for counseling interventions.